2004
DOI: 10.1038/sj.gt.3302210
|View full text |Cite
|
Sign up to set email alerts
|

Hydroporation as the mechanism of hydrodynamic delivery

Abstract: We have reported that a rapid tail vein injection of a large volume of plasmid DNA solution into a mouse results in high level of transgene expression in the liver. Gene transfer efficiency of this hydrodynamics-based procedure is determined by the combined effect of a large volume and high injection speed. Here, we show that the hydrodynamic injection induces a transient irregularity of heart function, a sharp increase in venous pressure, an enlargement of liver fenestrae, and enhancement of membrane permeabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
282
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(291 citation statements)
references
References 28 publications
6
282
1
2
Order By: Relevance
“…This technique was used in the clinical study 11 and in most of the studies in the pig. [5][6][7][8] It is very likely, as Zhang et al 12 have proposed, that swelling of the liver is the key to the hydrodynamic effect, by physically stretching hepatocytes and creating momentary breaks in the plasma membrane. We have previously discussed in detail that swelling of the liver can occur only if there is raised intrahepatic vascular pressure, and that raised vascular pressure can occur only if there is resistance to flow.…”
Section: Introductionmentioning
confidence: 99%
“…This technique was used in the clinical study 11 and in most of the studies in the pig. [5][6][7][8] It is very likely, as Zhang et al 12 have proposed, that swelling of the liver is the key to the hydrodynamic effect, by physically stretching hepatocytes and creating momentary breaks in the plasma membrane. We have previously discussed in detail that swelling of the liver can occur only if there is raised intrahepatic vascular pressure, and that raised vascular pressure can occur only if there is resistance to flow.…”
Section: Introductionmentioning
confidence: 99%
“…(i) The simplest, of course, is the injection of naked DNA, which in the skeletal or cardiac muscle leads to some expression of the injected genes; [1][2][3] however, this expression is very low and very variable from sample to sample. (ii) The hydrodynamic method consists in the very rapid injection through the mouse tail vein of a large volumes of DNA solution: it results in a very efficient transfection of liver cells, even though the procedure is somehow dangerous for the treated mice; [4][5][6] indeed, part of the mechanism is based on the transient heart failure resulting from the injection, which blocks the fluid distribution in the body and provokes a liquid overpressure in the liver. 6 (iii) For physical DNA transfer to superficial tissues like the skin or the leaves in the plant kingdom, the 'biolistic' approach ('jet injection' and 'gene gun') also leads to good transfection levels.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) The hydrodynamic method consists in the very rapid injection through the mouse tail vein of a large volumes of DNA solution: it results in a very efficient transfection of liver cells, even though the procedure is somehow dangerous for the treated mice; [4][5][6] indeed, part of the mechanism is based on the transient heart failure resulting from the injection, which blocks the fluid distribution in the body and provokes a liquid overpressure in the liver. 6 (iii) For physical DNA transfer to superficial tissues like the skin or the leaves in the plant kingdom, the 'biolistic' approach ('jet injection' and 'gene gun') also leads to good transfection levels. The commonly termed 'gene gun' consists in a device propelling plasmid-coated gold microparticles.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that intracellular delivery of plasmid DNA by hydrodynamic injection is through cell membranes with a high permeability. 32,33 After entering the cytosol, plasmid DNA was reported to enter the nucleus depending on the specific sequences of DNA. 34 In the present study, we did not observe any significant differences in the intranuclear amounts of DNA among the plasmids with different sequences (Figure 3).…”
Section: Inhibition Of Transgene Expression By Ifn-c L Zang Et Almentioning
confidence: 99%